Development and validation of a portfolio assessment system for medical schools in Korea - Dong Mi Yoo; A Ra Cho; Sun Kim (Journal of Educational Evaluation for Health Professions, 2020)
Purpose Consistent evaluation procedures based on objective and rational standards are essential for the sustainability of portfolio-based education, which has been widely introduced in medical education. We aimed to develop and implement a portfolio assessment system, and to assess its validity and reliability. Methods We developed a portfolio assessment system from March 2019 to August 2019 and confirmed its content validity through expert assessment by an expert group comprising 2 medical education specialists, 2 professors involved in education at medical school, and a professor of basic medical science. Six trained assessors conducted 2 rounds of evaluation of 7 randomly selected portfolios for the “Self-Development and Portfolio II” course from January 2020 to July 2020. These data are used inter-rater reliability was evaluated using intra-class correlation coefficients (ICCs) in September 2020. Results The portfolio assessment system is based on the following process; assessor selection, training, analytical/comprehensive evaluation, and consensus. Appropriately trained assessors evaluated portfolios based on specific assessment criteria and a rubric for assigning points. In the analysis of inter-rater reliability, the first round of evaluation grades was submitted, and all assessment areas except “goal-setting” showed a high ICC of 0.81 or higher. After the first round of assessment, we attempted to standardize objective assessment procedures. As a result, all components of the assessments showed close correlations, with ICCs of 0.81 or higher. Conclusion We confirmed that when assessors with an appropriate training conduct portfolio assessment based on specified standards through a systematic procedure, the results are reliable.